Cr (VI) adsorption from aqueous solutions on grafted chitosan. (21st February 2020) - Sanchez Ramirez, Diego O.; Periolatto, Monica; Carletto, Riccardo A.; Varesano, Alessio; Vineis, Claudia; Tonetti, Cinzia; Bongiovanni, Roberta
Abstract: Chitosan was grafted on the surface of a cotton gauze (20, 50, and 100 mg chitosan g −1 cotton) to improve its stability in aqueous solutions. The adsorption of hexavalent chromium ions from water on the grafted chitosan was evaluated to determine, by means of linear and nonlinear models, the kinetic and isotherm adsorption of the process. The kinetics of pseudo second‐order, pseudo first‐order, and adsorption isotherms type II were obtained, that is, a monolayer adsorption on nonporous adsorbents with physical adsorption was present. The most probable energy of adsorption corresponded to a physisorption with hydrogen bond interactions between chromium ions and ammonium groups. Moreover, three different cross‐sectional areas of hexavalent chromium ions were calculated and used to estimate the specific surface area employed by active sites to adsorb metal ions in terms of chitosan or cotton mass. Finally, the percentage of the area occupied by chromium ions on the surface was estimated by dividing the resulting specific surface area in terms of cotton mass by the specific surface area of cotton reported in literature. As a result, it was determined that the occupied area is between 6% (for 20 mg chitosan g −1 cotton)‐24% (for 100 mg chitosan g −1 cotton) from the total area of cotton. Abstract : Representation of adsorption: Cr(VI) + cross‐sectional area + active sites.